Determinants of MSMEs’ Adoption of Islamic Banking Products: The Role of Halal Lifestyle, Islamic Financial Literacy, and Trust - Ziadatul Nur Qholishoh; Heny Yuningrum; Muyassarah Muyassarah (Islamiconomic : Jurnal Ekonomi Islam, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in supporting Indonesia’s economic growth; however, the market share of Islamic banking remains relatively small compared to conventional banking, particularly among MSME actors. This indicates that MSMEs' use of Islamic banking products remains limited and may be influenced by behavioral and cognitive factors. Previous studies tend to examine financial literacy or trust separately, leaving a limited understanding of how halal lifestyle, Islamic financial literacy, and trust simultaneously influence MSMEs’ decisions to use Islamic banking products. This study aims to analyze the influence of halal lifestyle, Islamic financial literacy, and trust on MSMEs’ decisions to use Islamic banking products in Central Java. This study employs a quantitative approach, collecting primary data from 100 MSME actors via questionnaires and analyzing them using multiple linear regression. The results show that a halal lifestyle and trust have a positive and significant effect on MSMEs’ decisions to use Islamic banking products, whereas Islamic financial literacy has a significant negative effect, suggesting that higher literacy may encourage MSME actors to be more critical and selective in their choice of financial institutions. The three variables simultaneously explain 62.7% of the variation in MSME decisions, with trust identified as the most dominant factor. These findings contribute to the consumer behavior perspective in Islamic finance by integrating halal lifestyle, Islamic financial literacy, and trust to explain MSME financing decisions in Islamic banking.